M. Kostomarov and Kharkiv in the O. Rusov’s Letters to A. Kostomarova - Ворожбит, Ірина (V. N. Karazin Kharkiv National University Bulletin History of Ukraine. Ukrainian Studies: Historical and Philosophical Sciences, 2018)
This article deals with the publication of O. Rusov’s letters to A. Kostomarova. The letters contain the information about the work of Statistics Bureau of Kharkiv, local press characteristics and it’s social impact. The correspondence reveals the problem of M. Kostomarov’s memorization. The popularization of the sources of Ukraine local history actualizes the integral role of history for the Ukrainian society.